MOTIVASI PEGAWAI DAN DISIPLIN KERJA: FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN DI SMP NEGERI 2 BANDA ACEH - Dewi Maya Sari (Puslatbang KHAN, 2022)
Schools are the most frequently observed places of public service in the field of education. Customer satisfaction can be achieved through the provision of high-quality services in schools. The quality of administrative services analyzed in this study is the quality of administrative tasks such as academic, personnel, facilities and infrastructure, finance, student services, and institutional development. The main objective of this study is to determine the impact of motivation and work discipline on the service quality at SMP Negeri 2 Banda Aceh. The employees of SMP Negeri 2 Banda Aceh, a total of 59 people, are the subject of this study. The census method was used to carry out the sampling approach, resulting in 59 observations in this study. Multiple linear regression analysis was used to examine the data. The findings revealed that at SMP Negeri 2 Banda Aceh, employee motivation and work discipline had a positive and significant impact on the quality of services.